Conflict Exposure and Economic Welfare in Nigeria - John Chiwuzulum Odozi; Ruth Uwaifo Oyelere (Global Labor Organization (GLO), 2019)
Several papers have attempted to estimate and document the impact of conflict on numerous education, health and socioeconomic outcomes. One lesson from this research is the heterogeneity in the effect of violent conflict across and within countries. In this paper we attempt to estimate the casual impact of conflict in Nigeria on welfare related outcomes. The 2009 insurgence of Boko Haram and the Fulani herdsmen versus farmers conflicts have led to a significant increase in violent conflict in the North Eastern and Central parts of Nigeria. However, bouts of violent conflict has existed in different communities across Nigeria since independence. We estimate the general effect of conflict exposure on welfare, across Nigeria using the three waves of the Nigeria General Household Survey (GHS) combined with ACLED conflict data. Employing a fixed effect approach, our results suggest that recent and long term exposure to conflict increased poverty incidence, poverty gap and poverty severity in Nigeria.
Keywords: I10; I30; O1; D74; 330; Violence; Nigeria; Conflict; Boko Haram; Economic Welfare; Poverty